Automated writing evaluation : Catering for creativity - Norhazwanie, Jatin; Hafizoah, Kassim; Nor Yazi, Khamis (2022)
A lot of studies on creativity have been conducted for the past three decades as its role in every aspect of life has been more recognized. Against the backdrop of the use of technology during the COVID-19 pandemic, current studies have drawn more attention to the incorporation of creativity in technology-integrated teaching and learning. This paper calls into question the interplay between creativity as an essential learning skill and technology-driven language instructions emphasizing writing instructions. The AI-powered writing assistant, Automated Writing Evaluation (AWE), has been used in writing classrooms as a form of formative assessment to facilitate self-learning and expedite feedback. When used regularly, AWE is deemed effective in augmenting students’ writing performance, especially in an ESL environment. This paper links the models across three disciplines; writing, creativity, and technology, while accentuating the role of AWE in fostering creativity. Pedagogically, writing teachers who wish to embed creativity in their AWE-assisted lessons would benefit from this paper as they would gain a better understanding of the theoretical nature of the constructs.